Pengembangan Lembar Kerja Siswa (LKS) Materi Program Linier Bercirikan Problem Based Learning untuk Membangun Kemampuan Penalaran Matematis - Ani Afifah (FKIP Universitas Islam Jember, 2017)
This study aims to describe the process and develop students’ worksheets (LKS) characterized by problem based learning to build the ability of mathematical reasoning. This development refers to using the 4D model by Thiagarajan, Semmel, and Semmel (1974); they are define, design, and development. The validation results show that the students’ worksheets meet the valid, practical, and effective criteria. Students’ worksheets can build the mathematical reasoning ability shown by the percentage of students who are able to construct mathematical reasoning is 85.02%. In addition, the students’ responses and activities are in the category of either at least 60%.Key word: student worksheet, Problem Based Learning, mathematical reasoning